Pro-inflammatory polarization and colorectal cancer modulate alternative and intronic polyadenylation in primary human macrophages - Wilton, Joana; de Mendonça, Filipa Lopes; Pereira-Castro, Isabel; Tellier, Michael; Nojima, Takayuki; Costa, Angela M.; Freitas, Jaime; Murphy, Shona; Oliveira, Maria Jose; Proudfoot, Nicholas J.; Moreira, Alexandra (Frontiers in Immunology, 2023)
Macrophages are essential cells of the immune system that alter their inflammatory profile depending on their microenvironment. Alternative polyadenylation in the 3'UTR (3'UTR-APA) and intronic polyadenylation (IPA) are mechanisms that modulate gene expression, particularly in cancer and activated immune cells. Yet, how polarization and colorectal cancer (CRC) cells affect 3'UTR-APA and IPA in primary human macrophages was unclear. We isolated primary human monocytes from healthy donors, differentiated and polarized them into a pro-inflammatory state before carrying out ChrRNA-Seq and 3'RNA-Seq to quantify gene expression and characterize new 3’UTR-APA and IPA mRNA isoforms. Our results show that polarization of human macrophages from naïve to a pro-inflammatory state causes a marked increase of proximal polyA site selection in the 3'UTR and IPA events in genes relevant to macrophage functions. Additionally, we found a negative correlation between differential gene expression and IPA during pro-inflammatory polarization of primary human macrophages. As macrophages are abundant immune cells in the CRC microenvironment that either promote or abrogate cancer progression, we investigated how indirect exposure to CRC cells affects macrophage gene expression and 3'UTR-APA and IPA events. Co-culture with CRC cells alters the inflammatory phenotype of macrophages, increases the expression of pro-tumoral genes and induces 3’UTR-APA alterations. Notably, some of these gene expression differences were also found in tumour-associated macrophages of CRC patients, indicating that they are physiological relevant. Upon macrophage pro-inflammatory polarization, SRSF12 is the pre-mRNA processing gene that is most upregulated. After SRSF12 knockdown in M1 macrophages there is a global downregulation of gene expression, in particular in genes involved in gene expression regulation and in immune responses. Our results reveal new 3’UTR-APA and IPA mRNA isoforms produced during pro-inflammatory polarization of primary human macrophages and CRC co-culture that may be used in the future as diagnostic or therapeutic tools. Furthermore, our results highlight a function for SRSF12 in pro-inflammatory macrophages, key cells in the tumour response.